(untitled) - Halty Carrère, Maximo (Montreal, 1979)
The socio-economic progress of nations is inexorably tied to the choice of external technologies and effective strategies for internal technological development.
Keywords: Chuyển giao công nghệ,Technology transfer; Các nước đang phát triển,Developing countries